Consumer perceptions of nanotechnology applications in Italian wine - E. Chiodo; N. Casolani; G.M. Greehy; A. Fantini; M.B. McCarthy (Chiriotti Editori, 2015)
This paper examines Italian consumer acceptance of nanotechnology applications in wine production, surveying wine consumers from the Abruzzo Region. Conjoint and post-hoc segmentation analysis establishes how consumers value different wine product attributes and place them within the context of applications of nanotechnology. Consumers appear relatively unfamiliar with nanotechnology applications, both generally and specifically to food. Although, an overall rejection of the concept of "nano wine" is evident, low acceptance scores disguise a somewhat more open attitude to specific applications of the technology. In particular, consumers appear more receptive to applications that enhance certain wine attributes. Practical implications are discussed.